Factors Affecting on the Purchase Decision of Customers During Covid-19 Pandemic. A Study on Restaurant Industry of Pakistan - Dr.Rubina Jabeen; Hassaan Elahi; Shehu Aliyu, Dr. Mukhtar (UW Journal of Management Sciences, 2024)
Purpose: The current study has determine how word of mouth communication, price of a product and brand image, have influenced customers’ purchase decisions within the Pakistani restaurant industry during the Covid-19 pandemic. In other words, the research has examined the impact of word-of-mouth (WOM) communications, brand image, product price on the customers’ purchase decisions, especially under crisis situations like the Covid-19 pandemic, where the restaurant businesses of Pakistan were found to face numerous challenges in the form of loss of revenues, loss of jobs, and even closure of businesses. Design and Methodology: Quantitative methodology was utilized and multiple regression analysis has been used to determine the impact of WOM communications, price, and brand image on the customers’ purchase decisions. Findings: The findings of this research have shown that customers’ purchase decisions within the Pakistani restaurant industry were indeed influenced by WOM communications, brand image, and product price. Implications: The results of this study will help restaurant businesses in Pakistan to survive the challenges that were created by the pandemic, both before and after the lockdowns.